Performance Analysis of Wind Turbine - Denny Irawan; Zizin Anggun Kinanti (Kontribusia : Research Dissemination for Community Development, 2023)
Geographical conditions Indonesia has natural resources with good potential for the development of renewable energy. One of them is wind, wind is one of the natural resources in Indonesia that can be utilized because Indonesia is an archipelagic country that has a coastline of 81000 km. The largest wind energy resources are located at sea and near the coast. This wind resource can be used to generate electricity using a wind turbine, so this research is a prototype that can simulate a wind power plant (PLTB). The prototype of this wind power plant was tested by simulating the average wind speed in several regions of Indonesia. The wind speed is between 3 m/s – 7 m/s. The wind speed of the blower is regulated by using a dimmer in order to lower and accelerate the wind speed that sweeps the surface area of ​​the wind turbine. From the rotation of the wind turbine, it directly rotates the rotor so that the generator can produce electrical voltage. The output of the generator is connected to the load. The total load in this study is 15 Watt. By comparing the power that comes out of the generator and the power calculated using the formulation of the power that can be issued by the wind turbine, the efficiency of the generator used in this study can be obtained. The highest generator efficiency is when the wind speed is 6 m/s, with a value of only reaching 6.86%. The working efficiency of the generator can be stable above 5% when the wind speed is from 5 m/s – 7 m/s. The cause of the poor working efficiency of the generator is that the number of rotations produced by the wind turbine is not able to maximize the work of the generator.